Analysis performance of modified tamanu oil enhanced with additives as potential green alternative in metalworking fluids - Amiril Sahab, Abdul Sani; Puteri Humairah, Megat Ahmad Radzi; Ainaa Mardhiah, Sabri; Zubaidah, Zamri; Chandran, Nagulen; Norfazillah, Talib (Penerbit UTHM, 2022)
Mineral oils have long been utilized in industries as machining lubricants, which contributed to their depletion and hick in price and being non-biodegradable, harmful to the environment, and risk to health. Plant-based oil is more biodegradable, renewable, and environmentally friendly as a green alternative. However, in their crude state, plant-based oils are not up to par with the standard mineral oil used in lubrication in terms of high acidity, low-temperature performance, and oxidative instability. Further chemical modification and adding additives had to be made to improve the oil properties for industrial applications. This study focused on the performance of transesterification of Tamanu plant-based oil with Trimethylolpropane (MTO) and Pentaerythritol (MTOP), which mixed with 1% of Phosphonium Ionic Liquid (PIL) and 10% of Ammonium Ionic Liquid (AIL), producing a series of oil specimens; MTO, MTO+PIL1%, MTO+AIL%, MTOP, MTOP+PIL1%, and MTOP+AIL%. These samples are then subjected to physical analysis to determine the improvement of their properties in terms of kinematic viscosity and viscosity index as well as undergo a four-ball wear test to the determine the tribology aspects of the lubrication in terms of coefficient of frictions and wear scar diameter, in accordance with ASTM standard method. All the results were compared with commercial MWF which synthetic ester (SE) as reference oil. The result of viscosity index reveals that MTOP+PIL1% had the highest value of 178.76. MTO+AIL10% exhibits the lowest average COF (0.061) compared to other MTOs lubricants. Among MTOP, MTOP+PIL1% also had the lowest average COF which is 0.082. The addition of PIL1% to MTO and MTOP lowered the average scar diameter, 730.77 μm and 674.93μm respectively. With the enhanced properties from chemical modification and additives, Tamanu oil can be proposed as a green alternative for developing the metalworking fluid industries in the future.